Antigenic evolution of contemporary clade 2.3.4.4 HPAI H5 influenza A viruses and impact on vaccine use for mitigation and control. Issue 29 (29th June 2021) - Lewis, Nicola S; Banyard, Ashley C; Essen, Steve; Whittard, Elliot; Coggon, Amelia; Hansen, Rowena; Reid, Scott; Brown, Ian H
Abstract: Since 2003, highly pathogenic avian influenza (HPAI) viruses of the H5 subtype have been maintained in poultry, periodically spilling back into wild migratory birds and spread to other geographic regions, with re-introduction to domestic birds causing severe impacts for poultry health, production and food sustainability. Successive waves of infection have also resulted in substantial genetic evolution and reassortment, enabling the emergence of multiple clades and subtypes within the H5 2.3.4.4 HPAI viruses. Control of AI is principally through either culling or through vaccination using conventional vaccines. Here, we antigenically and genetically characterise the emerging 2020/21 H5NX clade 2.3.4.4 strains and assess cross-reactivity to putative vaccine strains using chicken antisera. We demonstrate significant antigenic differences between commercially available poultry vaccines and currently circulating viruses suggesting that vaccination options might be suboptimal in the current outbreaks.